Terapi Bermain Puzzle pada Anak Usia 3-6 tahun terhadap Kecemasan Pra Operasi - Aprina Aprina; Novri Ardiyansa; Sunarsih Sunarsih (Jurnal Kesehatan, 2019)
Problems that often appear before surgery are anxiety. Playing is an effective coping method to reduce anxiety experienced by children. This study aims to identify the effect of playing puzzle therapy on preoperative anxiety levels in the Children's Surgery Room of Dr. H. Abdul Moeloek Lampung Province. The design of this study was Quasy Experiment with the design of one group pretest-posttest. This type of quantitative research uses the technique of accidental sampling. The population in this study were preoperative patients. The analysis used is a parametic test of the t test dependent test. When the research began from July 12 to August 12 in the pediatric surgery oroom of Dr. H. Abdul  Moeloek Lampung Province. The results show the average anxiety score before therapy is playing puzzle is 64.30 and after giving therapy the role playing puzzle is 48.60. p-value obtained is 0,000 which indicates the difference in preoperative anxiety scores before and after getting puzzle play therapy.